Smart Three-Dimensional (3D) Hologram as an Innovative Teaching Tool in Virtual Learning Environment during Exigent Circumstances - Nadila Nadila; Mega Wirda Angriani; Diah Novrianty Utami; Dewi Nopita (Pancaran Pendidikan, 2021)
It cannot be denied that almost all aspects of human life are in gadgets. Gadgets are equipped with different types of applications that can make human activities more effective. Smart 3D hologram is one of the applications that can be downloaded and installed on a smartphone. Smart 3D Hologram is considered as the most advanced technology that gives several advantages in education such as helping teachers and students to view devices that cannot be seen in traditional teaching-learning, offering virtual teachers, and making teachers and students still connected. It also shows us the real-size object. This article intends to describe Smart 3D hologram, an innovative teaching tool for future education that can be used offline in students-parents’ smartphones in a virtual learning environment. It is hoped that smart 3D hologram can become a smart solution in facilitating students in learning during exigent circumstances.